2000
DOI: 10.1002/1097-4644(20010101)80:1<156::aid-jcb150>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Expression screening of factors binding to the osteocalcin bone-specific promoter element OC Box I: Isolation of a novel osteoblast differentiation-specific factor

Abstract: Contributing to bone-specific expression of the osteocalcin gene is the promoter element OC Box I (-99 to -76), which binds both Hox proteins and another nonhomeodomain factor (designated OCBP for osteocalcin-box binding protein) (Hoffmann et al. [1996] J Cell Biochem 61:310-324). OCBP correlates with increased promoter activity and may, therefore, be important to development or maintenance of the osteoblast phenotype. To identify OCBP candidates, we used a multimerized OC Box I sequence to screen a gammagt11 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 55 publications
(67 reference statements)
1
6
0
Order By: Relevance
“…Previous studies using promoter deletion constructs of the rat OC gene have shown that the initial 200 bp of the promoter can confer tissue-specific expression (38). This region contains a Runx-responsive motif and a homeodomain box that also binds an osteoblast-specific complex (54). Sequence analysis of this A, total RNA was isolated from various skeletal and soft rat tissues as described under "Materials and Methods."…”
Section: C/ebp Proteins Activate the Osteocalcin Gene Through A C/ebpsupporting
confidence: 83%
“…Previous studies using promoter deletion constructs of the rat OC gene have shown that the initial 200 bp of the promoter can confer tissue-specific expression (38). This region contains a Runx-responsive motif and a homeodomain box that also binds an osteoblast-specific complex (54). Sequence analysis of this A, total RNA was isolated from various skeletal and soft rat tissues as described under "Materials and Methods."…”
Section: C/ebp Proteins Activate the Osteocalcin Gene Through A C/ebpsupporting
confidence: 83%
“…However, our present study showed that the reduction of MK mRNA level because of the suppression of nucleolin transcription by the application of nucleolin antisense probe was about 50%. This phenomenon seems to be caused by following several reasons as follows: 1) transcriptional reduction of nucleolin was not complete even by the antisense probe application, probably because the nucleolin was a ubiquitously expressed gene in cells; 2) it is unknown whether the transcriptional regulation of MK by nucleolin is direct or indirect, and there may be another transcriptional pathway for the MK expression besides nucleolin (39,40); 3) translational disturbance of nucleolin induced by adding antisense probe may influence the stabilization of MK mRNA as shown in previous reports (41,42). It therefore seems important to disclose the molecular interaction between nucleolin and MK in the cellular biology of tooth germ development.…”
Section: Discussionmentioning
confidence: 79%
“…The OC box binding protein (30,31), a previously characterized non-HD protein complex in ROS 17/2.8 cells, was not observed in nuclear extracts from the normal ROB cells at any stage (Fig. 4A).…”
Section: Resultsmentioning
confidence: 99%
“…EMSA reaction mixtures were prepared using 10 fmol of radiolabeled probe and 2.5 to 5 g of nuclear extract according to the procedure developed for optimal HD protein binding (30). Briefly, the DNA-protein binding reactions were carried out at room temperature for 10 min.…”
mentioning
confidence: 99%